Development and Application of Analogous Materials for Fluid-Solid Coupling Physical Model Test - Mingyang Ren; Xiangjie Yin; Ningjing Li; Xuyang Wu; Heng Liu (Advances in Materials Science and Engineering)
The coupling effect between the stress field formed by rock mass and the seepage field formed by groundwater has an important impact on the stability of underground engineering. In order to conduct the fluid-solid coupling physical model test in the laboratory, it is necessary to develop suitable analogous materials. In this study, a new type of analogous material reflecting the fluid-solid coupling effect is developed with iron powder, barite powder, and quartz sand as aggregates, white cement as a cementing agent, and silicone oil as a regulator. Through a large number of orthogonal experiments, the influence laws of different material contents on the mechanical properties and permeability characteristics of analogous materials are obtained. In addition, a method for quickly determining the proportion of components in fluid-solid coupling analogous materials is also proposed. The developed analogous material is employed in the fluid-solid coupling physical model test of a deep tunnel. The variation laws of rock stress, displacement, and seepage pressure around the tunnel during construction are obtained, which verifies the feasibility of the developed analogous material.